Waste Management Based On Women's Empowerment In Air Lintang Sub District Muara Enim - Lidya, Eva; Sartika, Diana Dewi; Isyanawulan, Gita (Sociology Department Of Syiah Kuala University, 2017)
This research is intended to describe waste management based on womens empowerment in Air Lintang Sub District, Muara Enim Regency. It is a qualitative research. The techniques of collecting the data are in-depth interview, observation and documentation. Data analysis is conducted through reduction, data display and conclusion. The research of this study showed that there were three main aspects in general; they are a) Capacity Building, b) Cultural Change, and c) Structural adjustment. The form of capacity building are waste management and improvement of management skills. While, the cultural change, that is to change the mindset of disgusting garbage into high economic value. Structural adjustment is about the policy aspect that support the waste management based on womens empowerment. The three aspects included on waste management based on womens empowerment in Air Lintang Sub District. This description can be used as a model for waste management in other areas.Keywords : waste management, womens empowerment